A Language Theory of Discrimination - Lang, Kevin (Quarterly Journal of Economics, 1986)
Any advanced industrial society is composed of a number of speech communities with different verbal and nonverbal languages. In particular, in the United States blacks and whites and men and women have sharply differing methods of speaking and listening. This paper develops a model in which people can only work together if they "speak" the same language and in which it is costly to learn a second language. The competitive market will tend to minimize communication through segregation, but if interaction is required, the cost will be borne by the minority. A number of nontrivial predictions are derived from the model.